Respuesta :

Answer:

2(x + 1)(2x + 1)

Step-by-step explanation:

[tex]y = 2(2x^2 + 3x + 1)[/tex]

Factor the trinomial in parentheses.

Since a - b + c = 0, use shortcut. One real root is -1 and the factor is (x + 1). The other root is: [tex]\frac{-c}{a}= -1/2[/tex]

and the factor is [tex](x+\frac{1}{2})[/tex]

Factor form of y:

y = 2(x + 1)(2x + 1)

Answer:

  (2x +1)(2x +2)

Step-by-step explanation:

One factor is the sum of the tiles across the top of the figure: x+x+1 = 2x+1.

The other factor is the sum of the tiles down the left side of the figure: x+x+1+1 = 2x+2.

__

The factorization shown by the tiles is ...

  4x^2 +6x +2 = (2x +1)(2x +2)

ACCESS MORE